Patterns of basal body addition in ciliary rows in Tetrahymena (The Rockefeller University Press, 1975)
Most naked basal bodies visualized in protargol stains on the surface of Tetrahymena are new basal bodies which have not yet developed cilia. The rarity of short cilia is explained by the rapid development of the ciliary shaft once it begins to grow. The high frequency of naked basal bodies (about 50 percent) in log cultures indicates that the interval between assembly of the basal body and the initiation of the cilium is long, approximately a full cell cycle. Naked basal bodies are more frequent in the mid and posterior parts of the cell and two or more naked basal bodies may be associated with one ciliated basal body in these regions. Daughter cells produced at division are apparently asymmetric with respect to their endowment of new and old organelles.